2018
DOI: 10.4103/ijmr.ijmr_1417_16
|View full text |Cite
|
Sign up to set email alerts
|

A surface antigen of Orientia tsutsugamushi activates human monocyte-derived dendritic cells via nuclear factor-kB & p38 mitogen-activated protein kinase pathways

Abstract: Background & objectives:Scrub typhus is a chigger-borne disease caused by Orientia tsutsugamushi. The immunological reactions to O. tsutsugamushi infection are not completely understood. In this study, we investigated the response of dendritic cells (DCs) to a major 56-kDa scrub typhus antigen Sta56.Methods:Monocyte-derived human DCs were incubated with different concentrations of recombinant Sta56 and analyzed for maturation based on phagocytic capacity, the ability to induce T-cell proliferation, expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Further research on the CCKR signaling map, EGF receptor signaling pathway, FGF signaling pathway, PDGF signaling pathway, Wnt signaling pathway, and p53 pathway is needed in the future. Previous studies reported that the surface antigen of O. tsutsugamushi activates the nuclear factor-kB and p38 mitogen-activated protein kinase pathway and that intracellular invasion of O. tsutsugamushi is mediated by integrin signaling [ 26 ]. These signaling pathways were also identified in the present study ( Supplementary Table S4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Further research on the CCKR signaling map, EGF receptor signaling pathway, FGF signaling pathway, PDGF signaling pathway, Wnt signaling pathway, and p53 pathway is needed in the future. Previous studies reported that the surface antigen of O. tsutsugamushi activates the nuclear factor-kB and p38 mitogen-activated protein kinase pathway and that intracellular invasion of O. tsutsugamushi is mediated by integrin signaling [ 26 ]. These signaling pathways were also identified in the present study ( Supplementary Table S4 ).…”
Section: Discussionmentioning
confidence: 99%